PENGARUH MEDIA VIDEO TUTORIAL TERHADAP HASIL BELAJAR MENGGAMBAR MODEL DI KELAS VIII MTSN 4 PASAMAN BARAT - Yasifa Khairenisa; Abd. Hafiz (Universitas Negeri Padang, 2021)
This research is a quantitative research which aims to see and find out whether or not there is an effect of using video tutorial media on the learning outcomes of Model Drawing at MTsN 4 West Pasaman. The population of this study was all VIII grade students of MTsN 4 Pasaman Barat. As for the research sample, using class VIII A and class VIII B. The sampling of the two classes used the Simple Random Sampling technique). To analyze the data, the normality test, homogeneity test, and hypothesis testing were used to analyze the data. The conclusion of this study is that learning using video tutorial media has a significant effect on learning outcomes to draw models in class VIII MTsN 4 Pasaman Baarat.Keywords: Learning Media, Video Tutorials, Learning Outcomes